Assistive devices for manual materials handling in warehouses: a systematic literature review. Issue 11 (3rd June 2021) - Glock, Christoph H.; Grosse, Eric H.; Neumann, W. Patrick; Feldman, Andrew
Abstract : This paper evaluates how technical assistive devices for manual materials handling were analysed in the literature in a warehousing context. Works that discuss the economic and/or human factors impact of assistive devices on the warehousing system or the people employed therein were identified in a systematic literature review. Building on a conceptual framework proposed in this paper, our evaluation of the literature shows which types of assistive devices were analysed in the past, and from which perspective these devices were examined. Some works studied the devices exclusively from an operator well-being or an efficiency perspective, while several works analysed the devices' performance in terms of both dimensions. Several works contained in our literature sample highlighted trade-offs between both ergonomic and economic measures and, within the first category, between alternative ergonomic indicators, which shows that assistive devices have to be evaluated carefully in light of their intended application. The paper further identifies research gaps and emphasises the need to understand the interactions between human- and system-related variables that can be supported by assistive devices in designing effective manual materials handling systems.